PENGARUH TINGKAT PENDIDIKAN, PENDAPATAN, DAN STATUS KETENAGAKERJAAN TERHADAP FERTILITAS MELALUI USIA KAWIN PERTAMA DI KECAMATAN MENGWI - Wirasaba, Anak Agung Sagung Dinarmahari Akasasabda; Ayuningsasi, A.A. Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.07.TAHUN.2023DO - 10.24843/EEB.2023.v12.i07.p16, 2023)
The objectives to be achieved in this study are 1) to analyze the effect of education level, income, and employment status on age at first marriage in Mengwi sub-district, Badung district, 2) to analyze the effect of education level, income, and employment status on fertility in Mengwi sub-district, district Badung, and 3) Analyzing the indirect effect of education level, income, and employment status on fertility through age at first marriage in Mengwi District, Badung Regency. Respondents in this study were couples of childbearing age as many as 123 samples with a purposive combined accidental sampling method. The data analysis technique used path analysis. The results of the study stated that 1) Education level, income, and employment status had a significant effect on age at first marriage in Mengwi District, Badung Regency, 2) Education level and income had a significant effect on fertility, while employment status had no significant effect on fertility in Mengwi District, Badung Regency, and 3) Education level, income, and employment status affect fertility indirectly through age at first marriage in Mengwi District, Badung Regency